Narrative Review: Potential of Flavonoids from Moringa (Moringa oleifera Lam.) Leaves as Immunomodulators: Tinjauan Naratif: Potensi Flavonoid dari Daun Kelor (Moringa oleifera Lamk.) sebagai Imunomodulator - Poluan, Jesica Carine; Zubair, Muhammad Sulaiman; Ramadani, Arba Pramundita; Hayati, Farida (Universitas Tadulako, 2023)
Background: Moringa leaves (Moringa oleifera Lamk.) are plants from the Moringaceae family that have many properties and are often used empirically as traditional medicine. One of the benefits of M. oleifera leaves is immunomodulator, which functions to modulate the human immune system in both immunostimulants and immunosuppressants. Objectives: To provide information on the potential of flavonoids in M. oleifera leaves as immunomudulators developed as alternative therapies. Methods: Review of articles using original articles from national and international journals with the keywords